2015
DOI: 10.1038/srep09812
|View full text |Cite
|
Sign up to set email alerts
|

Genomic ancestry and ethnoracial self-classification based on 5,871 community-dwelling Brazilians (The Epigen Initiative)

Abstract: Brazil never had segregation laws defining membership of an ethnoracial group. Thus, the composition of the Brazilian population is mixed, and its ethnoracial classification is complex. Previous studies showed conflicting results on the correlation between genome ancestry and ethnoracial classification in Brazilians. We used 370,539 Single Nucleotide Polymorphisms to quantify this correlation in 5,851 community-dwelling individuals in the South (Pelotas), Southeast (Bambui) and Northeast (Salvador) Brazil. Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
142
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(172 citation statements)
references
References 27 publications
13
142
0
9
Order By: Relevance
“…Continental genomic ancestry in Latin America (and specifically, in Brazil) is correlated with a set of phenotypes, such as skin color and self-reported ethnicity, and social and cultural features, such as socioeconomic status (15)(16)(17). We observed a positive correlation across the three EPIGEN populations between SNP-specific Africans/Europeans F ST (a measurement of informativeness of ancestry) and SNP-specific F IT (a measurement of departure from Hardy-Weinberg equilibrium) …”
Section: Resultsmentioning
confidence: 99%
“…Continental genomic ancestry in Latin America (and specifically, in Brazil) is correlated with a set of phenotypes, such as skin color and self-reported ethnicity, and social and cultural features, such as socioeconomic status (15)(16)(17). We observed a positive correlation across the three EPIGEN populations between SNP-specific Africans/Europeans F ST (a measurement of informativeness of ancestry) and SNP-specific F IT (a measurement of departure from Hardy-Weinberg equilibrium) …”
Section: Resultsmentioning
confidence: 99%
“…In SCAALA (the discovery sample) rs12007907 MAF (corresponding to the A allele) was 25%, reflecting the remarkable African contribution to this admixed population. 45 In the ProAr cohort the frequency of this SNP was 23%, which reflects the closest genetic similarity of this population with the discovery sample. However, in the GALA II and Pelotas cohorts the MAFs were 7 and 11%, respectively, which may result in a lack of statistical power to detect an association.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the function of IL1RAPL might be more related to the Toll-like receptors subfamily than IL1R subfamily. 45 Interestingly, IL1RAPL1 has already been reported in two previous GWAS to be associated with cardiovascular disease 47 and autism. 19 Although this gene belongs to the IL1R family, it has been poorly studied, possible due to its localization in the X chromosome and consequent exclusion from genome-wide analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study also demonstrated that European ancestry is predominant in Pelotas (85.3%). 39 In our analyses, we dichotomized the variable skin colour as white (66.8%) and others (33.2%).…”
Section: Resultsmentioning
confidence: 99%